(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
Abstract. The paper analyzes structural imbalances of the Russian labor market under demographic decline, including the shrinking working age population, workforce aging, regional disparities, and challenges in migration policy. Solution pathways are proposed.